GAMIFICATION IN EDUCATION: MAKE LEARNING FUN AND EFFECTIVE - Ahadova Hulkaroy; Boyqorayeva Aziza Rizamat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In the article we consider the current topic of gamification in education as an effective tool for modern learning. Gamification is the application of game design elements and mechanics in the educational process to increase student motivation, improve learning, and develop creativity. The article examines examples of successful implementation of gamification in various educational scenarios, and also discusses the key advantages and challenges of this approach. We emphasize the importance of creating adaptive and innovative educational games that can adequately reflect the needs of modern learning and maintain student motivation at a high level.